2009
DOI: 10.1007/s00415-009-5022-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative autonomic testing in the management of botulism

Abstract: Even with mild neurological signs, patients with botulism frequently complain of autonomic symptoms. This study aimed at the evaluation of sudomotor and cardiovascular reflex functions by quantitative autonomic testing (QAT), which may identify patients with autonomic involvement but otherwise benign clinical presentation. Five patients with food-borne botulism were subjected to a structured questionnaire on autonomic symptoms, cardiac and neurological examination, and QAT after a median of 2 weeks (baseline) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…In line with that, animal studies in dogs demonstrated a significant reduction and even elimination of parasympathetic related bradycardia and atrial fibrillation, respectively, following botulinum toxin A injections into pericardial fat pads (Oh, et al, 2011, Tsuboi, et al, 2002. An attenuation of parasympathetic modulation on the heart has also been described in studies on the autonomic cardiac effects of botulism, reporting significant declines of parasympathetic test parameters that lasted longer than in sympathetic tests (Vita, et al, 1987), elevated resting heart rate, and LF/HF ratio (Topakian, et al, 2009).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In line with that, animal studies in dogs demonstrated a significant reduction and even elimination of parasympathetic related bradycardia and atrial fibrillation, respectively, following botulinum toxin A injections into pericardial fat pads (Oh, et al, 2011, Tsuboi, et al, 2002. An attenuation of parasympathetic modulation on the heart has also been described in studies on the autonomic cardiac effects of botulism, reporting significant declines of parasympathetic test parameters that lasted longer than in sympathetic tests (Vita, et al, 1987), elevated resting heart rate, and LF/HF ratio (Topakian, et al, 2009).…”
Section: Discussionsupporting
confidence: 56%
“…Considering previous findings from studies on the effect of botulinum toxin on the cardiac autonomic function (Chen, et al, 1999, Claus, et al, 1995, Meichsner and Reichel, 2005, Pokushalov, et al, 2015, Reichel, et al, 1998, Topakian, et al, 2009, Vita, et al, 1987, effects seem to be predominantly HRV depressive, i.e. decrease in coefficient of variation of heart rate (Claus, et al, 1995), R-R interval variation (Chen, et al, 1999), RMSSD (Meichsner and Reichel, 2005, Pokushalov, et al, 2015, Reichel, et al, 1998, TP (Meichsner and Reichel, 2005), and SDNN (Meichsner and Reichel, 2005, Pokushalov, et al, 2015, Vita, et al, 1987, and/or parasympatholytic (Dickson andShevky, 1923, Rosenblum, 1966), i.e.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…To our knowledge, this is the first case of Takotsubo-like myocardial dysfunction in a patient with botulism; however, we believe that this condition has likely also been observed previously in studies on autonomic dysfunction due to botulism ( 3 ). Autonomic failure due to botulism had been considered to account for some cases of sudden infant death syndrome ( 4 ) as well as arrhythmias and electrocardiographic changes in adults ( 5 ).…”
Section: Discussionsupporting
confidence: 79%
“…Both autonomic symptoms can be explained by an inhibition of the cholinergic parasympathetic nervous system. Autonomic symptoms due to botulinum toxin poisoning, including high resting heart rate, supine hypertension, orthostatic hypotension, and impaired baroreflex function were reported even in mild clinical courses [ 12 ]. Moreover, autonomic dysfunction can be the leading symptom of botulism type B [ 13 ].…”
Section: Discussionmentioning
confidence: 99%